Perlindungan Hukum terhadap Korban dalam Tindak Pidana Eksploitasi Seksual Anak (Studi Kasus Putusan Nomor 535/Pid.Sus/2019/PN Dps) - Ade Satriasa Maha Putra; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Warmadewa Press, 2021)
We must be aware of cases of crimes of sexual exploitation, especially in children, it is not enough if parents only but the government, society and the Indonesian Child Protection Commission must take a role in maintaining the continuity and protection of children. This new research aims to determine the legal protection of victims in criminal acts of sexual exploitation of children. This research type is normative research with a statutory approach and a conceptual approach. Legal materials consist of primary and secondary, then analyzed systematically. The results showed that legal protection for children from victims of sexual exploitation was given to legal subjects that had preventive or repressive characteristics. Furthermore, legal safeguards are essential to provide justice, order, certainty, benefit. The criminal sanctions given to the perpetrators of a criminal offense, namely for imprisonment for 7 (seven) years, reduced while the defendant is in detention and the penalty will be subject to a fine of IDR. 100,000,000 (one hundred million rupiah).